2016
DOI: 10.14260/jemds/2016/685
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Syphilis and Psoriasis

Abstract: Psoriasis is a chronic inflammatory skin disease with various triggering factors. Here we report a case of psoriasis coexisti ng with secondary syphilis which could have been a possible trigger for exacerbation of psoriasis. KEYWORDSPsoriasis, Secondary Syphilis. HOW TO CITE THIS ARTICLE:Kumar VS, Saradha KP, Anandan V, et al. Coexistence of syphilis and psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
123
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(131 citation statements)
references
References 6 publications
5
123
0
3
Order By: Relevance
“…There is one material [28] shown that intensity parameters  2 < 2, this condition represent the high covalent bonding that means there was broadening asymmetry around the environments glass [18]. Table 2 showed generally was observed that  2 >  4,6 [2,20,30,31,31,33] indicate the higher covalency of the ion-ligand bond lower symmetry of the Nd 3+ ion site. This result also explained that the higher intensity of hypersensitive transition and the nephelauxetic effect possessed by these glass [22].…”
Section: Judd-ofelt Analysismentioning
confidence: 94%
See 4 more Smart Citations
“…There is one material [28] shown that intensity parameters  2 < 2, this condition represent the high covalent bonding that means there was broadening asymmetry around the environments glass [18]. Table 2 showed generally was observed that  2 >  4,6 [2,20,30,31,31,33] indicate the higher covalency of the ion-ligand bond lower symmetry of the Nd 3+ ion site. This result also explained that the higher intensity of hypersensitive transition and the nephelauxetic effect possessed by these glass [22].…”
Section: Judd-ofelt Analysismentioning
confidence: 94%
“…The higher values of  4 and  6 [20,22,28,32,34] for the glasses indicated their mechanics have higher rigidity. Then, the spectroscopic quality factor known from  = ( 4 / 6 for to find the channel through which the excited metastable state to the ground state [2].…”
Section: Judd-ofelt Analysismentioning
confidence: 99%
See 3 more Smart Citations